2016
DOI: 10.4102/phcfm.v8i1.1210
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status, hypertension and body mass index in an urban black community in Mangaung, South Africa

Abstract: BackgroundA strong relationship exists between hypertension and body weight. Research has linked both higher blood pressure and body weight with lower vitamin D status.ObjectiveThis study assessed the vitamin D status of a low-income, urban, black community in South Africa, to examine whether serum levels of 25-hydroxy vitamin D [25(OH)D] are associated with hypertension and body mass index (BMI).MethodsData collected from 339 adults (25–64 years) from the Assuring Health for All in the Free State (AHA-FS) stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Low 25(OH)D concentrations have also been linked to an increased risk of obesity [ 31 ]; however, for the population investigated similar anthropometric markers were observed across differing 25(OH)D status. The lack of association between BMI and 25(OH)D concentrations was reported in another South African study, where recruitment was done in a province that neighbors the one from which we selected our volunteers [ 64 ]. This may indicate that the correlation between anthropometric markers and 25(OH)D status does not apply to black individuals living in South Africa, which necessitates further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Low 25(OH)D concentrations have also been linked to an increased risk of obesity [ 31 ]; however, for the population investigated similar anthropometric markers were observed across differing 25(OH)D status. The lack of association between BMI and 25(OH)D concentrations was reported in another South African study, where recruitment was done in a province that neighbors the one from which we selected our volunteers [ 64 ]. This may indicate that the correlation between anthropometric markers and 25(OH)D status does not apply to black individuals living in South Africa, which necessitates further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…39 A study conducted among hypertensive adults in an urban black community in Mangaung found that, despite the relationship between body mass index (BMI) and hypertension, vitamin D status appeared to have a protective effect, and those with an adequate vitamin D status appeared to be less vulnerable to hypertension despite an elevated BMI. 40 There appears to be a requirement for increased vitamin D among those with darker skin due to the decreased conversion of vitamin D from sunlight and a reciprocal relationship between vitamin D status and the rate of sputum culture conversion, 41 and seasonal reporting of TB, with higher incidences of TB in the winter months of reduced sunlight. 42 The need for vitamin D supplementation for all adult South Africans is still under review.…”
Section: Requirement For Vitamin D In South Africamentioning
confidence: 99%
“…These results are in agreement with some South African and global studies. 19,35,[37][38][39] Not all studies support lower serum 25(OH)D in females, however. 40 Additionally, Hovsepian et al studied vitamin D deficiency in Iran and concluded that women in that region experience more severe vitamin D deficiency than men only because of the clothing restrictions imposed upon them.…”
Section: Gender and 25(oh)dmentioning
confidence: 99%